Appreciative Listening to Tengger Folktales: Insights into Speech Acts and Social Functions of Language - Rusdhianti Wuryaningrum; Nindya Nurdianasari; Saleem Mohd. Nasim (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2026)
This study examines linguistic elements in Tengger folktales and their impact on the understanding of speech acts and the social functions of language. The analysis was conducted using both qualitative and quantitative approaches. Qualitative findings, based on linguistic analysis, indicate that the content of Tengger folktales holds strong potential as material for understanding speech acts and the social functions of language. These social functions are reflected in the narratives through messages conveyed in interactions among parents and children, among siblings, and between humans and their natural environment. From a pragmatic perspective, the understanding of speech acts can be developed through the design of teaching materials. Social functions of language can be naturally derived from the content and embedded social values of the folktales. Pragmatic aspects, particularly speech acts, need to be systematically developed within speech segments, which can be facilitated through instructional materials or learning media. This study employed both qualitative and quantitative instruments, with data categorisation based on contextual criteria. The results of the t-test indicate that appreciative listening to Tengger folktales has a significant effect on students’ understanding of speech acts and the social functions of language. These findings suggest that folklore-based appreciative listening is an effective approach for developing the social functions of language